Will macroprudential policy counteract monetary policy’s effects on financial stability? - Agur, Itai; Demertzis, Maria (Brussels, 2018)
"How does monetary policy impact upon macroprudential regulation? This paper models monetary policy’s transmission to bank risk taking, and its interaction with a regulator’s optimization problem.